Notch Signaling & Micro RNAs - two tumblers of neurogenesis and Gliomas - Zeeshan Javed,; Qamar Raza ,; Faiez Ahmad Shah ,; Haleema Sadia ,; Ayesha Alam,; Faiza Anum,; Mushtaq Ahmad Saleem ,; Shahid Raza , (Journal of the Pakistan Medical Association, 2020)
Abstract Gliomas are one of the most annihilating types of brain tumors having a high rate of annual incidence worldwide. Notch signaling is an evolutionary conserved pathway that regulates differentiation and development. Aberrations in Notch signalling pathways lead to severe pathological state such as the Gliomas. MicroRNAs (miRNAs) are the tiny molecules less than 200 bps in length and regulate a myriad of cellular processes. Categorically, miRNAs are divided in to oncogenic and tumor suppressor miRNAs. Accumulating data have identified miRNAs, which positively or negatively regulate Notch signaling in Gliomas. Here, we have assessed status of our understanding of the interplay between miRNA-base regulation of Notch signaling in gliomas, interaction between Notch signaling and other signaling cascades and have also discussed use of natural compounds that will help us get closer to personalized medicine for gliomas. Keywords: Notch signaling; MicroRNA; Therapeutic Targets; Continuous...